Institutional structures of the flexible assignment of personnel between enterprises: An economic comparison of Temporary Agency Work, Interim Management and Consulting - Dorothea Alewell; Katrin Bähring; Kirsten Thommes (Management Revue, 2005)
Temporary Agency Work, Interim Management and Consulting are three versions of the flexible assignment of personnel between enterprises, which are - with regard to their basic economic structure - more or less similar, but which are organised under thoroughly different contractual and legal regulations in Germany and in three more or less differentiated segments of the market. The paper aims at comparing these forms of flexible personnel assignment under empirical and institutional aspects from an economic perspective.
Keywords: 650; Interim Management; Consulting; Temporary Agency Work; flexible assignment of personnel between enterprises; institutional comparison; economic analysis